HUBUNGAN TINGKAT PENGETAHUAN TENTANG KANKER SERVIKS DENGAN PERILAKU DETEKSI DINI PADA PEGAWAI YANG BEKERJA DI FAKULTAS KEDOKTERAN UNIVERSITAS UDAYANA - Widyasari, Putu Kartika; Budiana, I Nyoman Gede; Megadhana, I Wayan; Putra, I Wayan Artana (Universitas Udayana, 2022)
Cervical cancer is a cancer caused by the oncogenic type of Human Papilloma Virus (HPV). This cancer ranks as the second common cancer in Indonesia. Among the 32,469 thousand new cases, there are 18,279 thousand of patients mortality. Cervical cancer can be prevented by early detection. The high prevalence of cervical cancer in Indonesia is due to the lack of public knowledge and awareness. In addition, the level of knowledge also affects the participation of women to conduct cervical cancer early detection. The faculty of medicine is very close to health issues and active to educate public regarding health. Therefore, the entire academic community is expected to be aware of and care about their respective personal health. This study is aimed to determining the correlation between cervical cancer knowledge level with early detection behavior towards employees at Faculty of Medicine, Udayana University. This study was an observational using a cross-sectional method and total sampling method for the data collection. Based on the results of the study, there was a significant relationship between the respondent’s knowledge level with cervical cancer early detection behavior (p-value <0.05). The group of respondents with insufficient knowledge, most of them said that they had never conducted early detection of cervical cancer as many as 8 people (80.0%). Meanwhile, most of the respondents with sufficient knowledge stated that they had conducted early detection of cervical cancer as many as 21 people (61.8%). Keywords : knowledge, cervical cancer, early detection, employees.